Analysis of current data on the use of topical rapamycin in the treatment of facial angiofibromas in Tuberous Sclerosis Complex. (29th August 2014) - Balestri, R.; Neri, I.; Patrizi, A.; Angileri, L.; Ricci, L.; Magnano, M.
Abstract Background Tuberous sclerosis complex (TSC) is an autosomal dominant neurocutaneous syndrome causing hamartomatous growths in multiple organs. Facial angiofibromas occur in up to 80% of patients and can be highly disfiguring. Treatment for these lesions has historically been challenging. Recently, topical rapamycin has been proposed as an effective option to treat angiofibromas but a commercially available compound has not yet been developed. Objectives The aim of this review is to analyse the current data on the use of topical rapamycin in the treatment of angiofibromas in TSC, focusing on the risk‐benefit profile. Methods A retrospective review of the English‐language literature was conducted. Results Sixteen reports describing the use of topical rapamycin in the treatment of angiofibromas in TSC were considered, involving a total of 84 patients. An improvement of the lesions has been shown in 94% of subjects, particularly if the treatment was started at early stages. Several different formulations (ointment, gel, solution and cream) with a wide range of concentrations (0.003%–1%) were proposed. Only 4 local adverse side‐effects were reported after the use of rapamycin solution. Conclusion Topical rapamycin can be considered a safe option for the treatment and the prevention of facial angiofibromas in younger patients, but the best formulation has not been established. Our review demonstrates that ointment and gel should be preferred, but it is not clear which concentration is optimal. Long‐term and comparative studies between topical rapamycin and ablative techniques are required to establish which treatment has a better outcome and lower recurrence rate.